The characterisation of the Spiritual Christian: In conversation with God according to 1 Corinthians 2 - Dirk van der Merwe (HTS Teologiese Studies/Theological Studies, 2018)
Irrespective of the short academic history of Christian spirituality, a vast number of academic and popular publications ensued and is still dynamically growing. Many definitions have been proposed to define (Christian) spirituality. Spirituality is also no longer connected only to religion, although in this research the focus will fall on Christian spirituality. This research intends to partake in the continuing academic dialogue to define Christian spirituality. Christian spirituality is interpreted from the perspective of the divine-human conversation. This research consists of three sections. In the first section, a working definition of Christian spirituality is formulated. In the second section, various aspects that constitute spiritualities are distinguished and discussed. In the last section, the constituents of Christian spirituality are pointed out and are reviewed from a conversational perspective. The focus will be on ‘the experience of the divine’ when living a life that resonates with the Christian life.